The development of a heat assisted section rolling process for strip - Mohd Zaidi, Sidek (2013)
This research aims to examine the feasibility of a new concept in section rolling of thick strip, which either could not be rolled at present due to cracking at bent corners. Whereas, the second moment of area of sections could be increased through sharpened corners and increased gauge thickness. A heat assisted section rolling process is proposed. This process is based on application of high intensity heat on the inner surface of the strip, immediately prior to rolling. To investigate the new section rolling concept, the following work has been carried out. Firstly, the material property of the S450 steel has been determined using the Gleeble simulator, followed by thermal conductivity tests. Since a freon was used to increase temperature gradient, the heat transfer coefficient for the freon-hot surface interaction was determined. Finally, the four point hot bending tests were conducted to validate the simulation model. For this purpose, a hot bending test rig was designed and fabricated, utilizing an halogen heater as the heat source. The results between experiment and simulation were compared and a good correlation was found. Then, finite element analyses of a single pass hot rolling process has been adopted to investigate the neutral axis shift and section thickening effects. It is revealed that localised heating creates bulging on the compressed surface. The bulged surface affects the both neutral axis and thickening of the formed parts. This research has demonstrated that localised heating has a potential to be employed in section rolling operations. It shows that the neutral axis of the bent region shifted closer to the tensile surface would reduce the tendency for surface cracking. In addition, the increase in thickness that arises at a bend would enhance the stiffness of rolled sections. Ultimately a process window for heat assisted section rolling has been established.